Enhancement in the Electrocatalytic and Optoelectronic Performance of Cost-Effective Counter Electrode VO2 for Dye-Sensitized Solar Cell (DSSC) - Varsha Yadav; Rahul Bhatnagar; Upendra Kumar (Advances in Condensed Matter Physics)
Dye-sensitized solar cells (DSSCs) have garnered significant attention in the scientific community for more than two decades due to their cost-effectiveness, convenient manufacturability, little toxicity, and straightforward preparation methodology. In this study, we present a cost-effective alternative to the platinum electrode for DSSCs, which serves as the counter electrode. The utilization of vanadium oxide nanoparticles as counter electrodes (CEs) in DSSCs has been the subject of research due to its enhanced stability, cost-effectiveness, and favorable photovoltaic characteristics. The device has been fabricated in configuration of fluorine-doped tin oxide (FTO)||TiO2||ruthenium (II) dye (N719)||iodide—triiodide electrolyte||VO2 (counter electrode)||FTO and investigate their photovoltaic performance. The utilization of X-ray diffraction (XRD) analysis has provided insights into the crystalline properties of VO2, indicating that it exists in a crystalline phase with a crystalline size measuring 43.19 nm and a lattice strain of 1.68 × 10−3. The utilization of a field emission scanning electron microscope (FESEM) that is equipped with an energy dispersive X-ray spectrum reveals a dense microstructure characterized by a uniform distribution of vanadium (V) and oxygen (O) across the whole surface. The Raman spectroscopic examination of VO2 reveals the existence of many Raman bands, thereby confirming the presence of the monoclinic phase. Cyclic voltammetry measurements were employed to investigate the catalytic activity of the CE toward the electrolyte. The photovoltaic performance of the manufactured device was examined by I–V measurement, revealing a notable open circuit voltage (Voc) and efficient power conversion efficiency when compared to the other materials that were evaluated.